External parasites of small ruminants [ a practical guide to their prevention and control - Bates, Peter [ (Peter George)] (CABI, 2012)
Sheep and goats are farmed throughout the world for meat, fiber, milk and leather. These small ruminants are very susceptible to external parasites, which has significant implications for their health and welfare as well as the quality and value of the nd products for which they are farmed. This book gives practical guidance on preventing and controlling ectoparasites that contribute to disease and infection in sheep and goats, discussing types of parasites, the diseases they cause and what methods of control are available, as well as wider implications such as animal welfare and environmental impacts.